2013
DOI: 10.2147/ceor.s49659
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of taxes on nonalcoholic beverages and high-in-fat foods as a means to prevent obesity trends

Abstract: BackgroundAs part of the efforts to curb obesity, a new focus seems to be put on taxing foods that are perceived as being associated with obesity (eg, sugar-sweetened beverages and foods high in fat, sugar, and salt content) as a policy instrument to promote healthier diets.ObjectiveTo assess the possible effects of such taxation policies by identifying and analyzing all studies which investigate the impact of price increases on consumption, caloric intake, or weight outcomes.MethodsElectronic data bases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 95 publications
0
35
0
1
Order By: Relevance
“…The role of macro‐level environmental factors such as taxation, advertising/marketing, product price and placement have yet to be studied in relation to young children's SSB consumption. However, a recent systematic review suggested that taxation may not be effective in reducing SSB consumption in adults, and the impact on children may therefore be questionable .…”
Section: Discussionmentioning
confidence: 99%
“…The role of macro‐level environmental factors such as taxation, advertising/marketing, product price and placement have yet to be studied in relation to young children's SSB consumption. However, a recent systematic review suggested that taxation may not be effective in reducing SSB consumption in adults, and the impact on children may therefore be questionable .…”
Section: Discussionmentioning
confidence: 99%
“…A nivel poblacional, cambios en la demanda (como estrategias de educación alimentaria, 20,21 regulación de la comercialización de alimentos, 22 cambios en el etiquetado nutricional) 23 y en la oferta (regulación del contenido de nutrientes de alimentos, como sodio, 24 grasas trans, 25 azúcares, políticas impositivas, 26,27 tamaños de porciones) deberían profundizarse para promover una alimentación más saludable.…”
Section: Discussionunclassified
“…19 Initiatives towards the promotion of a healthy diet targeted at this population and school setting have been implemented in Argentina through healthy candy stands and canteens. Changes should be deepened at a population level, both * Indicates the comparison between the total for 2007 and the total for 2012. in terms of demand (such as nutrition education strategies, 20,21 food marketing regulation, 22 nutrition labeling modifications) 23 and offer (for example, regulation of food nutritional content, such as sodium, 24 trans fats, 25 and sugar, tax policies, 26,27 and serving sizes) so as to promote a healthier diet.…”
Section: Discussionmentioning
confidence: 99%